2016
DOI: 10.1103/physrevb.93.054102
|View full text |Cite
|
Sign up to set email alerts
|

Ordered helium trapping and bonding in compressed arsenolite: Synthesis ofAs4O6·2He

Abstract: Compression of arsenolite has been studied from a joint experimental and theoretical point of view. Experiments on this molecular solid at high pressures with different pressure-transmitting media have been interpreted thanks to state-of-the-art ab initio calculations. Our results confirm arsenolite as one of the most compressible minerals and provide evidence for ordered helium trapping above 3 GPa between adamantane-type As 4 O 6 cages. Our calculations indicate that, at relatively small pressures, helium es… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 28 publications
3
42
1
Order By: Relevance
“…It is worth noting that 1) no coexistence of ars and incl was observed when ars powder was used instead of a single crystal, 2) the incl crystal structure proposed by Sans et al. is fully consistent with our crystal structure determination, and 3) pressure‐induced amorphization (PIA) of ars was observed at around 20 GPa when it was subjected to HP without any PTM or with a PTM other than He . The last finding was corroborated by using DFT computations of ars elastic constants, which indicated that it becomes mechanically unstable at 19.7 GPa and violates Born stability criteria.…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…It is worth noting that 1) no coexistence of ars and incl was observed when ars powder was used instead of a single crystal, 2) the incl crystal structure proposed by Sans et al. is fully consistent with our crystal structure determination, and 3) pressure‐induced amorphization (PIA) of ars was observed at around 20 GPa when it was subjected to HP without any PTM or with a PTM other than He . The last finding was corroborated by using DFT computations of ars elastic constants, which indicated that it becomes mechanically unstable at 19.7 GPa and violates Born stability criteria.…”
Section: Introductionsupporting
confidence: 86%
“…We recently discovered that helium can enter nonporous crystals of cubic arsenic(III) oxide, arsenolite, and determined the crystal structure of the as‐formed As 4 O 6 ⋅ 2 He clathrate by using single‐crystal X‐ray diffraction . This was also independently found by Sans and co‐workers for powdered arsenolite samples …”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…In β-Bi 2 O 3 , we note that powder samples were used instead of single crystals because the β phase is a metastable phase that has been stabilized in submicron-sized particles and nanoparticles [71] and in N-and Y-doped Bi 2 O 3 [22,72]. The use of gaseous environments (i.e., He or Ne) as pressure-transmitting media assures a larger hydrostatic regime than liquid media; however, some studies have shown that the use of gas can modify the compressibility of certain materials with porous or open framework structures when gas molecules can enter into the large voids of the crystalline structure with the increase of pressure, as in As 4 O 6 [73], SiO 2 [74], and other porous materials [75]. In this regard, β-Bi 2 O 3 contains large channels in its structure, which are formed by the presence of LEPs from Bi atoms.…”
Section: Mechanical and Dynamical Stabilitymentioning
confidence: 99%
“…Additionally, previous works have reported the structural characterization of As 4 O 6 under compression by means of angle dispersive x-ray diffraction (XRD) measurements using different pressure-transmitting media (PTMs) [8,10]. In those works it was shown that arsenolite is one of the most compressible non-hydrated minerals.…”
mentioning
confidence: 99%